Long-term Combination Therapy With α-Blockers and 5α-Reductase Inhibitors in Benign Prostatic Hyperplasia: Patient Adherence and Causes of Withdrawal From Medication - Hueih Ling Ong; Chun-Hou Liao; Hann-Chorng Kuo (International Neurourology Journal, 2016)
Purpose To investigate long-term therapeutic effects and patient adherence to a combination therapy of a 5α-reductase inhibitor and an α-blocker and to identify causes of withdrawal from medication in patients with clinical benign prostatic hyperplasia (BPH). Methods BPH patients with lower urinary tract symptoms (LUTS) receiving combination therapy with follow-ups for 1–12 years were retrospectively analyzed. Therapeutic effects were assessed at baseline and annually by measuring International Prostatic Symptoms Score, quality of life index, total prostate volume (TPV), maximal flow rate, voided volume, postvoid residual volume and prostate-specific antigen level. Causes of discontinued combination therapy were also investigated. Results A total of 625 patients, aged 40–97 years (mean, 73 years) were retrospectively analyzed. All measured parameters showed significant improvements after combination therapy. Three hundred sixty-nine patients (59%) discontinued combination therapy with a mean treatment duration of 2.2 years. The most common reasons for discontinued treatment were changing medication to monotherapy with α-blockers or antimuscarinics (124 patients, 19.8%), receiving surgical intervention (39 patients, 6.2%), and LUTS improvement (53 patients, 8.5%). Only 64 patients (10.2%) were loss to follow-up and 6 (1.0%) discontinued combined treatment due to adverse effects. Smaller TPV after short-term combination treatment caused withdrawal from combination therapy. Conclusions BPH patients receiving long-term combination therapy showed significant improvement in all measured parameters. Changing medication, improved LUTS and choosing surgery are common reasons for discontinuing combination herapy. A smaller TPV after short-term combination treatment was among the factors that caused withdrawal from combination therapy.